2018
DOI: 10.3390/app8122637
|View full text |Cite
|
Sign up to set email alerts
|

TEG Design for Waste Heat Recovery at an Aviation Jet Engine Nozzle

Abstract: Finite element model (FEM)-based simulations are conducted for the application of a thermoelectric generator (TEG) between the hot core stream and the cool bypass flow at the nozzle of an aviation turbofan engine. This work reports the resulting requirements on the TEG design with respect to applied thermoelectric (TE) element lengths and filling factors (F) of the TE modules in order to achieve a positive effect on the specific fuel consumption. Assuming a virtual optimized TE material and varying the convect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
(43 reference statements)
0
7
0
1
Order By: Relevance
“…However, the efficiencies of these materials are improving, and different types of installation architectures may improve the power density to such an extent that they become more attractive for larger scale use. Indeed, Ziolkowski et al [171] has shown that when placing thermoelectric generators between the hot core stream and cold bypass flow of a gas turbine engine, a feasible design range can be obtained, with a beneficial effect on aircraft specific fuel consumption. The TRL for the implementation of thermoelectric heat sinks in aircraft has been placed at between 3 and 4 [102].…”
Section: Thermal Storage and Conversion Heat Sinksmentioning
confidence: 99%
“…However, the efficiencies of these materials are improving, and different types of installation architectures may improve the power density to such an extent that they become more attractive for larger scale use. Indeed, Ziolkowski et al [171] has shown that when placing thermoelectric generators between the hot core stream and cold bypass flow of a gas turbine engine, a feasible design range can be obtained, with a beneficial effect on aircraft specific fuel consumption. The TRL for the implementation of thermoelectric heat sinks in aircraft has been placed at between 3 and 4 [102].…”
Section: Thermal Storage and Conversion Heat Sinksmentioning
confidence: 99%
“…Other alternative locations worth exploring include the aircraft engine and nozzle, where a large amount of heat is expended throughout the course of the flight [109]. However, as the geometry at these areas is slightly more complicated than that of a flat surface, more considerations are included in designing the device.…”
Section: In Commercial Airplanesmentioning
confidence: 99%
“…For commercial planes, there are multiple possible locations to install thermoelectric devices-the most common being the fuselage, where low-temperature thermoelectrics are utilized for powering WSNs [153,154]. Looking toward further usage of thermoelectrics in commercial aviation, models have been constructed around the installation of thermoelectric generators at the plane engine nozzles [109]. As previously mentioned, the temperature gradient in this area can be large.…”
Section: Environmental and Situational Considerationsmentioning
confidence: 99%
“…1.65 kW per engine. With higher nozzle surface coverage and improved heat sink design, the obtained power output could be increased to even 3 kW [153]. An approach where exhaust gases were used to increase the temperature of the hot side of the TEG module was recently experimentally investigated on a jet engine as well [154].…”
Section: High Temperature Difference Applications Of Tegs In Airplanesmentioning
confidence: 99%